Type I interferon responses of common carp strains with different levels of resistance to koi herpesvirus disease during infection with CyHV-3 or SVCV. Issue 87 (April 2019) - Adamek, Mikolaj; Matras, Marek; Dawson, Andy; Piackova, Veronika; Gela, David; Kocour, Martin; Adamek, Jerzy; Kaminski, Rafal; Rakus, Krzysztof; Bergmann, Sven M.; Stachnik, Magdalena; Reichert, Michal; et al.
Abstract: Carp from breeding strains with different genetic background present diverse levels of resistance to viral pathogens. Carp strains of Asian origin, currently being treated as Cyprinus rubrofuscus L., especially Amur wild carp (AS), were proven to be more resistant to koi herpesvirus disease (KHVD; caused by cyprinid herpesvirus 3, CyHV-3) than strains originating from Europe and belonging to Cyprinus carpio L., like the Prerov scale carp (PS) or koi carp from a breed in the Czech Republic. We hypothesised that it can be associated with a higher magnitude of type I interferon (IFN) response as a first line of innate defence mechanisms against viral infections. To evaluate this hypothesis, four strains of common carp (AS, Rop, PS and koi) were challenged using two viral infection models: Rhabdovirus SVCV ( spring viremia of carp virus ) and alloherpesvirus CyHV-3. The infection with SVCV induced a low mortality rates and the most resistant was the Rop strain (no mortalities), whereas the PS strain was the most susceptible (survival rate of 78%). During CyHV-3 infection, Rop and AS strains performed better (survival rates of 78% and 53%, respectively) than PS and koi strains (survival rates of 35% and 10%, respectively). The evaluation of virus loads and virus replication showed significant differences between the carp strains, which correlated with the mortality rate. The evaluation of type I IFN responses showed that there were fundamental differences between the virus infection models. While responses to the SVCV were high, the CyHV-3 generally induced low responses. Furthermore, the results demonstrated that the magnitude of type I IFN responses did not correlate with a higher resistance in infected carp. In the case of a CyHV-3 infection, reduced type I IFN responses could be related to the potential ability of the virus to interfere with cellular sensing of foreign nucleic acids. Taken together, the results broaden our understanding of how common carp from different genetic strains interact with various viral pathogens. Highlights: Differences in mortality rates during SVCV and CyHV-3 infections were recorded in carp strains. The higher resistance of the Rop strain was related to lower virus load and replication. The magnitude of type I IFN response was not positively correlated with survival. CyHV-3 has an ability to limit IFN response induced by sensing viral DNA by cells.